Android-Based Muhammadiyah Organization Introduction Application Using the Linear Congruent Generator Method - muntahanah muntahanah; Rozali Toyib; Joka Jasri (Jurnal Media Computer Science, 2023)
The aim of the research is to build an android-based application for introducing the Muhammadiyah organization using a Linear Congruent Generator, to introduce Muhammadiyah teachings to many people more easily and to provide knowledge about Muhammadiyah worship procedures. its function in the development of Islam in Indonesia, which so far has been carried out through branches and branches throughout the archipelago. The solution to this problem is to introduce Muhammadiyah teachings, it requires the help of technology that is currently developing. By using Android, we can introduce Muhammadiyah to more people because it can be used anywhere and anytime. In the application, it will be displayed starting from the history of the founding of Muhammadiyah, Muhammadiyah teachings and Muhammadiyah practical worship. It is hoped that with this application in Test results The nature of the Linear Congruent Method (LCM) method is that repetition occurs at a certain time period or after a certain number of times of generation so that there are no repetitions in the problem, the choice of constant values ​​must be correct and the existence of a shuffling process, helps overcome the problem of Linear Congruential Generator (LCG).